(untitled) (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
Agreements serve as one of legal instruments in the tourism sector, ensuring legal certainty and protection for the contracting parties. In the context of tour package agreements, the principle of Pacta Sunt Servanda affirms that every contract must be performed properly as agreed. However, in reality, the implementation of such agreements may not always proceed smoothly, particularly when confronted with force majeure events such as natural disasters, pandemics, or government regulations restricting travel activities. This study aims to analyze the regulation of Pacta Sunt Servanda and force majeure under the Indonesian Civil Code (KUHPerdata), as well as to examine the legal implications of force majeure on the enforcement of tour package agreements. The research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that although Pacta Sunt Servanda grants binding force to the contents of a contract, this principle may be subject to exceptions when a valid force majeure event occurs, as stipulated in Articles 1244 and 1245 of the Civil Code. Under such conditions, the debtor may be released from liability or granted a postponement in fulfilling contractual obligations. These implications highlight the necessity of balancing legal certainty with contractual fairness. Therefore, the inclusion of a force majeure clause in tourism agreements is essential as a legal foundation for dispute resolution in an industry highly vulnerable to external disruptions. Perjanjian merupakan salah satu instrumen dalam bertransaksi di bidang pariwisata yang berfungsi menjamin kepastian dan perlindungan hukum bagi para pihak. Dalam konteks perjanjian paket wisata, asas Pacta Sunt Servanda menegaskan bahwa setiap perjanjian yang dibuat secara sah wajib dilaksanakan. Namun, dalam praktiknya, pelaksanaan perjanjian tidak selalu berjalan lancar, terutama ketika muncul keadaan memaksa (force majeure) seperti bencana alam, pandemi, atau kebijakan pemerintah yang membatasi aktivitas perjalanan. Penelitian ini bertujuan untuk menganalisis pengaturan asas Pacta Sunt Servanda dan force majeure dalam KUHPerdata, serta menelaah implikasi hukum dari keberadaan force majeure terhadap perjanjian paket wisata. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Hasil kajian menunjukkan bahwa meskipun asas Pacta Sunt Servanda memberikan kekuatan mengikat terhadap isi perjanjian, namun prinsip ini dapat mengalami pengecualian apabila terbukti terjadi force majeure sebagaimana diatur dalam Pasal 1244 dan 1245 KUHPerdata. Dalam kondisi demikian, debitur dapat dibebaskan dari kewajiban atau diberikan penundaan pelaksanaan prestasi. Implikasi ini menegaskan pentingnya keseimbangan antara kepastian hukum dan keadilan kontraktual. Oleh karena itu, keberadaan klausul force majeure dalam perjanjian sangat penting sebagai dasar hukum penyelesaian sengketa dalam industri pariwisata yang rawan terhadap gangguan eksternal.